2006
DOI: 10.1073/pnas.0605216103
|View full text |Cite
|
Sign up to set email alerts
|

Exploring atomistic details of pH-dependent peptide folding

Abstract: Modeling pH-coupled conformational dynamics allows one to probe many important pH-dependent biological processes, ranging from ATP synthesis, enzyme catalysis, and membrane fusion to protein folding͞misfolding and amyloid formation. This work illustrates the strengths and capabilities of continuous constant pH molecular dynamics in exploring pH-dependent conformational transitions in proteins by revisiting an experimentally well studied model protein fragment, the C peptide from ribonuclease A. The simulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
101
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(105 citation statements)
references
References 24 publications
4
101
0
Order By: Relevance
“…It should be noted that our simulations used a recently improved implicit solvent model, GB with a simple switching (GBSW) (14,15). Its application to protein folding studies has been validated by comparison between simulated and experimental folding behavior for a series of helix-and ␤-sheet-based peptides (15,17).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…It should be noted that our simulations used a recently improved implicit solvent model, GB with a simple switching (GBSW) (14,15). Its application to protein folding studies has been validated by comparison between simulated and experimental folding behavior for a series of helix-and ␤-sheet-based peptides (15,17).…”
Section: Methodsmentioning
confidence: 99%
“…Briefly, this method enables molecular dynamics simulations to be performed simultaneously with the titration of ionizable side chains under an external pH condition in the presence of a generalized Born (GB) implicit solvent model. Combined with a state-of-the-art conformational sampling protocol, the REX algorithm (13), benchmark studies demonstrated that REX-CPHMD simulations can offer accurate and robust first-principles prediction for protein pK a values (16) and atomically detailed molecular mechanisms for pHdependent protein folding (17,18). It should be noted that our simulations used a recently improved implicit solvent model, GB with a simple switching (GBSW) (14,15).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5] In the continuous approach, an additional titration degree of freedom is added for every titratable site and the titration degrees of freedom are propagated alongside conformational dynamics. [6][7][8] Among these methods, the continuous pH molecular dynamics (pHMD) method 7,8 based on λ dynamics, 9 which will be referred to as CpHMD hereafter, has been successfully applied to pK a predictions 10 and pH-dependent protein folding 11 and conformational dynamics. 12,13 The first version of the CpHMD technique makes use of the generalized Born (GB) implicit-solvent model for propagating both conformational and titration coordinates and the temperature-based a) Present address: Department of Pharmaceutical Sciences, University of Maryland, Baltimore, Maryland 21201, USA.…”
Section: Introductionmentioning
confidence: 99%
“…The strength of the charge-charge interaction depends on the distance as 1/r, which makes them, at short distances, comparable in strength with Lennard-Jones (LJ) interactions. However, the charge-charge interactions are also long-range and they do not decay as quickly as LJ with the increase in distance [40][41][42][43][44]. All this makes charge-charge interactions an important contributor not only to protein stability, but also to the overall behavior of polypeptide sequences as heteropolymers [45,46].…”
Section: Introductionmentioning
confidence: 99%